Integrating Local Wisdom in Project-Based Learning to Improve Post-Pandemic English Learning - Huda Shofyana, Maila; Giri Aditama, Madya; Iqbal Nugroho, Harliyandri; Tri Asmoro, Heri (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The project-Based Learning (PjBL) method is the recommended method to be applied in the Merdeka Belajar curriculum. The application of Proj-BL based on local wisdom allows students to freely express and maximize creativity in doing assignments and also as a medium for cultural preservation and the introduction of various kinds of local wisdom, as well as a socialization event in the environment. It is qualitative research with the purpose is to analyze the local wisdom-based Project Based Learning (PjBL) teaching method applied by English teachers at SMA and SMK levels in Batang Regency in post-pandemic learning in the Merdeka Belajar curriculum. The objects of this study are 20 English teachers in Batang regency. The result shows that the application of PjBL based on local wisdom by teachers is commonly used in culture, Tourism, peoples, local industry, entrepreneurship, folklore, and myth scopes. This study reveals several examples of the application PjBl in Language Learning, which can be referenced for readers and teachers. It is also found that this method can develop students’ soft skills such as sympathy, empathy, self-confidence, problem-solving, and teamwork; also this method can maximize students' & teachers’ competencies in learning